Nucleus Reuniens Lesion and Antidepressant Treatment Prevent Hippocampal Neurostructural Alterations Induced by Chronic Mild Stress in Male Rats - Kafetzopoulos, V; Kokras, N; Sousa, N.; Antoniou, K; Sotiropoulos, I; Dalla, C (Neuroscience, 2021)
The hippocampus-prefrontal cortex circuit plays a major role in stress and in the neurobiology of depression and its treatment. Disruption of this circuit by lesioning the thalamic nucleus reuniens (RE) has been shown to prevent the detrimental effects of chronic mild stress on prefrontal cortex neuroplasticity indices in male rats. However, it remains unknown whether hippocampal neurostructural response to stress is modified by RE lesion. In the present study, adult male rats were subjected to the chronic mild stress model of depression and were treated with either vehicle or an antidepressant (i.e. sertraline). Moreover, a group of animals was subjected to RE lesion before stress exposure with or without sertraline treatment. We demonstrated that chronic mild stress induced hippocampal CA1 dendritic atrophy and this was prevented by pre-stress RE lesion to the same extent that antidepressant treatment reversed it. The present findings highlight the importance of hippocampal-prefrontal cortex communication in chronic stress effects on hippocampal neuroplasticity and contribute to the elucidation of the role of RE in neurostructural changes underlying stress-driven depression and its treatment.
Keywords: *Hippocampus; *Midline Thalamic Nuclei; Animals; Antidepressive Agents/pharmacology; chronic mild stress; Dendrites; Hippocampus; Male; Neural Pathways; nucleus reuniens; Prefrontal Cortex; Rats; Sertraline